Mamee Double Decker / Muhammad Aiman Muhamad Nasir - Muhamad Nasir, Muhammad Aiman (Faculty of Business and Management, 2023)
Internship, also known as industrial training, is a 12-credit course that must be successfully completed by all undergraduate students at Universiti Teknologi Mara (UiTM) in order for them to graduate. Students in the Faculty of Business and Management (FBM) have 24 weeks to work in a public or private company of their choice to learn as much as they can. The course is also important because it can lead to professional learning experiences that give students valuable hands-on work in their field of study or career goals. Through this kind of hands-on learning, students can learn about and develop both hard and soft skills, as well as explore and develop possible careers. It can also give companies the chance to get new ideas and energy into their offices while preparing students for jobs as full-time, fully committed workers in the future. During this practical training, students will put their knowledge and skills to use because they will be put in a difficult real-world work situation. In this approach, the objective of preparing students to become potential employers in their particular sectors will also be accomplished successfully. For my industrial training, I decided on Mamee Double Decker since it is a well- established company and I would like to gain experience in a food manufacturing setting. I selected it for my internship so I could learn useful skills and meet the university's criteria to earn my bachelor's degree. So, I wrote this report to share what I learned and observed during my internship at this company. This report has a link to my most current resume, which I will use to look for jobs after I graduate. It is in the section for students' profiles. I also wrote about the company's background, location, management style, organisational structure, and products. In the reflection part, I wrote about the experience, the things I learned, and the benefits I got from going to the programme. In the next part, I talk about how I could improve these four areas and talk about the SWOT analysis that this agency came up with, which is shown in the diagram. In the last part of my report, which also has relevant documents, I talk about the results of the whole writing process.